Estudio de la factibilidad para el encausamiento con enrocado para proteger el puente ubicado sobre el Río Congo en el recinto La Carlota del cantón Balzar - Párraga Muñoz, Miguel Leonardo (2015)
Speaking generally of the rivers, we find an exact idea how it is formed, it is usually extremely problematic due to an empirically based on the banks of a river population. It is therefore necessary to know the historical behavior, rainfall and river development in recent years, and derive feasibility for protection against possible natural disasters that commonly generated in winter times. A riprap protection using systems within the area to be protected be it a bridge over any river where there is a population, it is important the need to manage hydrologic and hydraulic data to undertake a feasibility design protection…….